2018
DOI: 10.1002/jcp.26960
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: MicroRNA‐150 contributes to ischemic stroke through its effect on cerebral cortical neuron survival and function by inhibiting ERK1/2 axis via Mal

Abstract: Ischemic stroke, caused by the blockage of blood supply, is a major cause of death worldwide. For identifying potential candidates, we explored the effects microRNA-150 (miR-150) has on ischemic stroke and its underlying mechanism by developing a stable middle cerebral artery occlusion (MCAO) rat model. Gene expression microarray analysis was performed to screen differentially expressed genes associated with MCAO. We evaluated the expression of miR-150 and Mal and the status of ERK1/2 axis in the brain tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Since ligustrazine is considered as a neuroprotective agent in the management of Vd disease by suppressing Pc12 cell apoptosis (32), it was also hypothesized that mir-150 knockdown might protect against Vd by inhibiting Pc12 cell apoptosis. a previous study demonstrated that mir-150 knockdown functions in the survival of cerebral cortical neurons (33). in the present study, compared with the empty vector group, HoXa1 overexpression significantly inhibited mir-150 mimic-induced Pc12 cell apoptosis, which suggested that mir-150 might mediate the biological function of Pc12 cells via HoXa1.…”
Section: Discussionsupporting
confidence: 67%
“…Since ligustrazine is considered as a neuroprotective agent in the management of Vd disease by suppressing Pc12 cell apoptosis (32), it was also hypothesized that mir-150 knockdown might protect against Vd by inhibiting Pc12 cell apoptosis. a previous study demonstrated that mir-150 knockdown functions in the survival of cerebral cortical neurons (33). in the present study, compared with the empty vector group, HoXa1 overexpression significantly inhibited mir-150 mimic-induced Pc12 cell apoptosis, which suggested that mir-150 might mediate the biological function of Pc12 cells via HoXa1.…”
Section: Discussionsupporting
confidence: 67%
“…miRNAs participate in the posttranscriptional regulation of gene expression and are involved in neurogenesis, development, and maintenance of neuronal phenotype (Kaur et al, 2013;Yapijakis, 2020). miRNA-dependent regulation of neuronal survival and ischemic stroke is a research topic of growing interest (Guo et al, 2017;Lv et al, 2019;Wu F. et al, 2019). Several studies have reported that a considerable number of miRNAs are altered following focal cerebral ischemia, some of which have been implicated in the modulation of inflammation (Jaenisch et al, 2016), autophagy (Zhao et al, 2017), apoptosis (Zhang and Meng, 2019), and oxidative stress (Kanagaraj et al, 2014) by regulating target protein levels.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulating ERK1/2 pathway activity is associated with neuronal survival in ischemic stroke models in vivo and in vitro [ 37 , 38 ]. ERK1/2 acts as a neuroprotective agent by inhibiting postischemic oxidative stress and mitochondria-dependent apoptosis of neural cells [ 39 , 40 ]. ERK1/2 activation can promote the phosphorylation of CREB, increase the expression of prosurvival protein Bcl-2, inhibit ischemia-induced neuronal apoptosis, and enhance neuronal survival [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%